Television courtroom broadcasting : distraction effects and eye-tracking - Lambert, Paul (Intellect, 2012)
Cameras in court or television courtroom broadcasting (TCB) is topical and controversial. This book explores one important aspect of the TCB debate. It explores one of the central concerns in the TCB debate, namely whether there are effects of television cameras in the courtroom. Are the people in court affected or distracted by the television cameras? This is a frequent concern in the debate regarding TCB. Many people have argued that TCB will adversely affect or distract the participants in a case where cameras are permitted. Eye-tracking can track and record where individual persons in the.